2013
DOI: 10.5604/20831862.1059297
|View full text |Cite
|
Sign up to set email alerts
|

Specific Sites of Bone Expansion Depend to the Level of Volleyball Practice in Prepubescent Boys

Abstract: The purpose of this study was to investigate the effect of 18 months of high and low levels of volleyball practice on bone acquisition. 130 prepubescent boys (mean age 11.4 ± 0.7) were divided into a high-level training group (HLG), low-level training group (LLG), and controls. Bone mineral content (BMC) and bone area at the whole body, lumbar spine L2-L4, femoral neck of the dominant leg, and right and left radius were measured using dual-photon X-ray absorptiometry. Enhanced BMC resulted from high-training v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
7
9
1
Order By: Relevance
“…These effects were more marked in femoral neck BMC and were better observed in SJ and CMJ in VB than BB. These findings are in accordance with results of previous studies, which indicate that bone mass was positively related to physical activity in prepubertal period (19,20) and was dependent on ground forces reactions on bony attachments produced by exercise types (8,9).…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…These effects were more marked in femoral neck BMC and were better observed in SJ and CMJ in VB than BB. These findings are in accordance with results of previous studies, which indicate that bone mass was positively related to physical activity in prepubertal period (19,20) and was dependent on ground forces reactions on bony attachments produced by exercise types (8,9).…”
Section: Discussionsupporting
confidence: 95%
“…These findings are similar to those described in other studies performed in prepubescent VB and BB who clearly have an enhancement of BA at most of weightbearing and nonweight-bearing bones (19,20). Dias Quiterio et al (9) found that participation in high-impact sports such as basketball, handball, or gymnastics during adolescence was associated with greater bone benefits, particularly on BA in total body, lumbar spine, and both upper and lower limbs than controls.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations